Principal visionary leadership and teacher instructional innovation: mediating roles of teacher workplace well-being and collaboration - Yang, Chuang; Xu, Zeqing (Frontiers in Psychology, 2026)
Instructional innovation is essential for preparing schools for the future and nurturing innovative talent. This study, grounded in vision communication theory, examines how principal visionary leadership contributes to teachers’ instructional innovation through psychological and organizational mechanisms. Survey data from 813 teachers in China were analyzed using structural equation modeling and bootstrapping. Results indicate that visionary leadership directly predicts instructional innovation and indirectly influences it through teacher workplace well-being and collaboration, with well-being exerting the strongest mediating effect. Furthermore, a chain pathway was identified: visionary leadership enhances teachers’ workplace well-being, which fosters greater collaboration and ultimately promotes innovation. These findings extend research on teacher innovation, provide cross-cultural evidence of visionary leadership’s effects, and suggest that school leaders can promote sustainable innovation by enhancing vision communication, cultivating a supportive school culture, and integrating teacher well-being with formal and informal collaboration structures.